Evidence for a peak shift in a humoral response to helminths: age profiles of IgE in the Shuar of Ecuador, the Tsimane of Bolivia, and the U.S. NHANES. - Aaron D Blackwell; Michael D Gurven; Lawrence S Sugiyama; Felicia C Madimenos; Melissa A Liebert; Melanie A Martin; Hillard S Kaplan; J Josh Snodgrass (Public Library of Science (PLoS), 2011)
The peak shift model predicts that the age-profile of a pathogen's prevalence depends upon its transmission rate, peaking earlier in populations with higher transmission and declining as partial immunity is acquired. Helminth infections are associated with increased immunoglobulin E (IgE), which may convey partial immunity and influence the peak shift. Although studies have noted peak shifts in helminths, corresponding peak shifts in total IgE have not been investigated, nor has the age-patterning been carefully examined across populations. We test for differences in the age-patterning of IgE between two South American forager-horticulturalist populations and the United States: the Tsimane of Bolivia (n=832), the Shuar of Ecuador (n=289), and the U.S. NHANES (n=8,336). We then examine the relationship between total IgE and helminth prevalences in the Tsimane.Total IgE levels were assessed in serum and dried blood spots and age-patterns examined with non-linear regression models. Tsimane had the highest IgE (geometric mean =8,182 IU/ml), followed by Shuar (1,252 IU/ml), and NHANES (52 IU/ml). Consistent with predictions, higher population IgE was associated with steeper increases at early ages and earlier peaks: Tsimane IgE peaked at 7 years, Shuar at 10 years, and NHANES at 17 years. For Tsimane, the age-pattern was compared with fecal helminth prevalences. Overall, 57% had detectable eggs or larva, with hookworm (45.4%) and Ascaris lumbricoides (19.9%) the most prevalent. The peak in total IgE occurred around the peak in A. lumbricoides, which was associated with higher IgE in children <10, but with lower IgE in adolescents.The age-patterning suggests a peak shift in total IgE similar to that seen in helminth infections, particularly A. lumbricoides. This age-patterning may have implications for understanding the effects of helminths on other health outcomes, such as allergy, growth, and response to childhood vaccination.